Hot or not: Quantifying isothiocyanates in plants, soil, and other media - Octavia Hogaboam; Viola A. Manning; Catherine L. Reardon; Kristin M. Trippe (Biosensors and Bioelectronics: X)
Isothiocyanates (ITCs) are bioactive compounds produced by plants in the Brassicales that serve as natural defense mechanisms against pests and pathogens, and provide sharp, hot, and pungent flavors to plants like wasabi, mustards, and horseradish. In agricultural settings, natural and synthetic ITCs are used to biofumigate soils prior to planting; however, because residual ITCs can inhibit germination or plant growth, (i.e. soils are “hot”), caution is necessary when fields are replanted. Current methodologies that measure ITCs are labor intensive and require expensive instrumentation. Therefore, there is a critical need for rapid, reliable, and inexpensive methods that detect ITCs in a variety of plant and soil matrices. This study describes the development and validation of the SaxAPIL biosensor, which uses an ITC-responsive promoter to drive expression of a bioluminescent reporter in Pseudomonas fluorescens SBW25 to quantify ITCs. Our results indicate that SaxAPIL can be used in a high throughput microplate-based assay to detect ITCs in a dose-dependent manner in solutions, plant- and seed meal-derived extracts, and soils amended with green manure or seed meals. Our results clearly demonstrate that SaxAPIL is a robust biosensor for the detection and quantification of aliphatic ITCs in plants and soil. The methodology presented here may be adapted to provide more efficient and less expensive methods to measure ITCs in industrial, health, and life science applications.